(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2019)
The aim of the study was to assess the groundwater quality for agricultural irrigation in Masis Region, which is one of the traditional agricultural areas of Armenia. In order to evaluate the quality of groundwater in the study area, 27 groundwater samples were collected and analyzed to obtain various parameters such as electrical conductivity (EC), pH, as well as Na+, K+, Ca2+, Mg2+, HCO3 –, CO32– and Cl– contents. The detected concentrations were interpreted and compared with different international irrigation standards. Study results led us to the conclusion that to control the process of soil salinization in the Masis Region (especially in the eastern and southern parts) the groundwater from great depths should be used for irrigation of agricultural areas, and an alternative source of irrigation water should be found in Ranchpar Village due to unsuitability of groundwater for these purposes.